2019
DOI: 10.1007/s12289-019-01499-y
|View full text |Cite
|
Sign up to set email alerts
|

Picture-frame testing of woven prepreg fabric: An investigation of sample geometry and shear angle acquisition

Abstract: This paper examines different concepts in relation to the picture-frame test for shear characterization of a woven prepreg fabric. The influence of the sample arms is investigated by means of cut slits as well as removed transverse tows. Shear angles are obtained using Digital Image Correlation (DIC) and also from images taken during the test which are processed for fiber angles directly from the weave texture. The image processing relies on the Hough transform in MATLAB. The concept of constant shear strain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Three‐dimensional (3D) digital image correlation (DIC) and 3D point tracking (3DPT) systems have proven their efficiency in being able to perform noncontact inspections 29 . They provide accurate quantitative information of structural deformations, full‐field strain maps, geometry profiles, and modal parameters 30 over a wide range of civil and mechanical engineering systems such as rotating machinery, 31 bridges, 32 railroad tracks, 33 and composite materials 34 . In recent years, computer vision and stereophotogrammetry approaches have gained substantial popularity for WTB monitoring and dynamic behavior characterization because of their noncontact nature 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Three‐dimensional (3D) digital image correlation (DIC) and 3D point tracking (3DPT) systems have proven their efficiency in being able to perform noncontact inspections 29 . They provide accurate quantitative information of structural deformations, full‐field strain maps, geometry profiles, and modal parameters 30 over a wide range of civil and mechanical engineering systems such as rotating machinery, 31 bridges, 32 railroad tracks, 33 and composite materials 34 . In recent years, computer vision and stereophotogrammetry approaches have gained substantial popularity for WTB monitoring and dynamic behavior characterization because of their noncontact nature 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…The parameters used for the model are listed in Table 2. The prepreg material used in this study exhibits nonlinear and rate-dependent behavior as was shown in previous publications [8,26]. The representation of, respectively, the bending and shear behavior through the constant moduli E and G deserve some elaboration.…”
Section: Air Pocket Evaluationmentioning
confidence: 61%
“…Concerning the bending behavior, the value of Young's modulus, E, was found by using the static deflection from a cantilever test [27]. Concerning the shear behavior, the value of the shear modulus, G, was found from the initial behavior recorded through bias-extension and picture-frame tests [8,26] and also from considerations on providing sufficient resistance against crumpling of the mesh. The coefficient of friction µ was measured in connection with a previous study [8].…”
Section: Air Pocket Evaluationmentioning
confidence: 99%
“…It is therefore important to employ a technique that correctly measures the actual shear angle, specifically during the bias extension tests in the so-called pure-shear zone. In contrast, the picture frame test does not require external shear angle measurement, because an overall uniform shear deformation exists within the acceptable limits over the entire specimen [10,16,17]. As a consequence, the determination of the material shear angle can be done using the rigid frame angle.…”
Section: Shear Angle Measurementmentioning
confidence: 99%
“…Despite the inherent drawbacks and delicacy of implementation, the two test methods are equally popular for measuring the shear properties of biaxial fabrics. The picture frame test is considered to create a uniform shear deformation of the entire specimen [10,11,16,17]. This deformation mode makes the post-test analysis relatively straightforward.…”
Section: Introductionmentioning
confidence: 99%